(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article analyzes the role of artificial intelligence technologies and smart contracts in legal relations, and the legal mechanisms for resolving disputes that arise during their use. Proposals for improving national legislation in this area have also been developed.